2015
DOI: 10.1002/mrm.25831
|View full text |Cite
|
Sign up to set email alerts
|

Golden ratio sparse MRI using tiny golden angles

Abstract: This work enables sparse, golden-ratio-based imaging with balanced SSFP sequences. Magn Reson Med 75:2372-2378, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 31 publications
0
85
0
Order By: Relevance
“…However, for application of cardiac CINE where data is acquired continuously without interruption, in combination with balanced SSFP sequence, the golden angle step can lead to rapidly changing eddy currents, resulting in strong image artefacts [27]. Recently, a new sequence of smaller irrational angles (49.75°, 32.039°, 27.198°, 23.628°) called as tiny golden angle has been introduced for 2D golden radial acquisition [28]. Provided a sufficient number of k-space radial profiles are acquired, it has been shown that the smaller tiny golden angle of 23.628° results in k-space sampling distribution similar to standard golden angle of 111.246°, but with much better eddy current performance.…”
Section: Methodsmentioning
confidence: 99%
“…However, for application of cardiac CINE where data is acquired continuously without interruption, in combination with balanced SSFP sequence, the golden angle step can lead to rapidly changing eddy currents, resulting in strong image artefacts [27]. Recently, a new sequence of smaller irrational angles (49.75°, 32.039°, 27.198°, 23.628°) called as tiny golden angle has been introduced for 2D golden radial acquisition [28]. Provided a sufficient number of k-space radial profiles are acquired, it has been shown that the smaller tiny golden angle of 23.628° results in k-space sampling distribution similar to standard golden angle of 111.246°, but with much better eddy current performance.…”
Section: Methodsmentioning
confidence: 99%
“…Using the imaging parameters proposed by Voit et al as a guide, we developed a protocol with spatial resolution on the order of 2.0 × 2.0 mm and temporal resolution on the order of 40 ms or better. To identify the acceptable limits of acceleration, we acquired a fully sampled ECG‐gated breath‐hold cine MRI data (image acquisition matrix = 144 × 144, repetition time [TR] = 2.7 ms) from a male patient (age, 63 y), retrospectively undersampled the k‐space using a TGA , and found that acceleration factor (R) ≥ 12 (i.e., 12 k‐space lines per image, temporal resolution = 32 ms) produces high data fidelity as defined by structural similarity index ≥ 0.95 (http://binarystore.wiley.com/store/10.1002/mrm.26918/asset/supinfo/mrm26918-sup-0001-suppinfo01.docx?v=1&s=0bbbe220d3be1ee9b7e8dcbdf1609493b807dc5c).…”
Section: Methodsmentioning
confidence: 99%
“…The second extension is to apply this framework to other self‐calibrated PI, including SPIRiT, Gridding Operator GRAPPA (GROG) and so on. Moreover, the proposed framework can also be used in cases with a small golden‐angle radial trajectory or other similar non‐Cartesian trajectories.…”
Section: Discussionmentioning
confidence: 99%